THE INFLUENCE OF POVERTY RATE, LOCAL REVENUE, AND CAPITAL EXPENDITURE ON HUMAN DEVELOPMENT QUALITY IN REGENCIES/CITIES IN BALI PROVINCE - A A Gde Agung Bismaputra (Adisam Publisher, 2025)
Millennials are currently regarded as the dominant generation within the workforce of companies in Indonesia. However, available data indicate that millennial employees report the lowest levels of job satisfaction. Low job satisfaction among employees can reduce workplace productivity and effectiveness. This literature review aims to identify the factors that influence job satisfaction among millennial employees in Indonesia. The study adopts a literature review method by analyzing ten peer-reviewed scientific articles as data sources. The findings of this study are expected to help millennial employees understand the various factors affecting their job satisfaction, thereby enabling them to work more productively and comfortably.